The Real Consequences of Market Segmentation - Chernenko, Sergey; Sunderam, Adi (Review of Financial Studies, 2012)
We study the real effects of market segmentation due to credit ratings by using a matched sample of firms just above and just below the investment-grade cutoff. These firms have similar observables, including average investment rates. However, flows into high-yield mutual funds have an economically significant effect on the issuance and investment of the speculative-grade firms relative to their matches, especially for firms likely to be financially constrained. The effect is associated with the discrete change in label from investment- to speculative-grade, not with changes in continuous measures of credit quality. We do not find similar effects at other rating boundaries.